2017
DOI: 10.1099/mic.0.000532
|View full text |Cite
|
Sign up to set email alerts
|

Binding host proteins to the M protein contributes to the mortality associated with influenza–Streptococcus pyogenes superinfections

Abstract: The mortality associated with influenza A virus (IAV) is often due to the development of secondary bacterial infections known as superinfections. The group A streptococcus (GAS) is a relatively uncommon cause of IAV superinfections, but the mortality of these infections is high. We used a murine model to determine whether the surface-localized GAS M protein contributes to the outcome of IAV-GAS superinfections. A comparison between wild-type GAS and an M protein mutant strain (emm3) showed that the M3 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
(50 reference statements)
1
10
0
Order By: Relevance
“…While capable of causing death as a primary viral invader, the majority of influenza virus-related deaths arise from secondary bacterial infections (38,42,67), including pneumonia (14,83). Studies in pigs (31,33,35,56,57), ferrets (7,17,27,40), and mice (9,73) demonstrate that these complex polymicrobial infections require contributions from the virus (37,39), the host (41,63,66,68,70), and the bacteria (8,22,50) to progress to death, with distinct interactions between the virus and an infected host influencing the severity of secondary bacterial infections. Since these secondary bacterial infections can naturally affect both humans and pigs, there is significant interest in understanding the host-pathogen interactions that are associated with severe secondary bacterial infections, including cytokine and host cell contributions (16,21,31,33,58).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While capable of causing death as a primary viral invader, the majority of influenza virus-related deaths arise from secondary bacterial infections (38,42,67), including pneumonia (14,83). Studies in pigs (31,33,35,56,57), ferrets (7,17,27,40), and mice (9,73) demonstrate that these complex polymicrobial infections require contributions from the virus (37,39), the host (41,63,66,68,70), and the bacteria (8,22,50) to progress to death, with distinct interactions between the virus and an infected host influencing the severity of secondary bacterial infections. Since these secondary bacterial infections can naturally affect both humans and pigs, there is significant interest in understanding the host-pathogen interactions that are associated with severe secondary bacterial infections, including cytokine and host cell contributions (16,21,31,33,58).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, GAS and influenza share a common seasonality, and work with an influenza virus: GAS model of superinfection has shown an association with necrotizing fasciitis (49,51). Our group has been working with an influenza virus-GAS model of superinfection in mice (12) to evaluate the contribution of influenza viruses and bacteria toward the severity of secondary bacterial infections (22,81). Our previous comparison of influenza viruses and bacterial species showed that the virus strain used for primary inoculation can have a profound effect on susceptibility to secondary infection with GAS, Streptococcus pneumoniae, and Staphylococcus aureus (81).…”
Section: Introductionmentioning
confidence: 99%
“…However, even if GAS is inoculated several days after influenza virus infection, a considerable proportion of mice die from invasive GAS infections , indicating that factors other than HA and other viral surface proteins can also enhance bacterial invasion. M3 protein is an important pathogenic factor for invasive GAS infections in influenza virus–GAS superinfection . According to this study, GAS mutants lacking M3 protein cannot cause invasion.…”
Section: Pathogenetic Mechanisms Of Invasive Gas Infections Caused Bymentioning
confidence: 89%
“…Even though S. pyogenes plays an important role in co-infection processes 9,10 , sparse information is available and only a few articles are focusing on co-infections involving this bacteria in combination with influenza A 912 . S. pyogenes is an important pathogen with a large number of situation dependent virulence factors causing angina, toxin mediated shock syndrome, and pneumonia 1315 .…”
Section: Introductionmentioning
confidence: 99%
“…During the binding process of influenza A onto cells, sialic acids are removed through the effect of the viral proteins hemagglutinin (HA) and neuraminidase (NA) 16 . In this way, presence of influenza A virus can support bacterial adhesion because bacterial binding to cells without sialic acid is much easier 1,9 . Okamoto et al .…”
Section: Introductionmentioning
confidence: 99%